KERJA SAMA ANTARA BADAN NARKOTIKA NASIONAL DENGAN POLISI NASIONAL TIMOR LESTE DALAM PENANGANAN KASUS PEREDARAN GELAP NARKOTIKA DI INDONESIA - Agnes Florince Destemyca Bella (2023)
Drug crime is an extraordinary crime that afflicts all countries in the world because drugs can wipe out an entire generation of people from a country. The National Narcotics Board has made efforts to eradicate narcotics syndicate networks throughout 2022. Drug abuse is still a big problem for Indonesia, including the province of East Nusa Tenggara (NTT). NTT is a potential area for drug transportation and marketing because of its open geographical conditions and borders with two countries, Timor Leste and Australia, greatly facilitate the entry of drug dealers into Indonesia. BNN as the leading sector in handling narcotics cases in Indonesia must strive for various ways so that this does not happen. One way is for BNN to collaborate with neighboring countries, such as Timor Leste, which will be discussed in this study. The approach predicted by BNN is a soft power approach by carrying out collaborative activities. This cooperation with Timor Leste is a form of bilateral relations established by the two countries to jointly overcome and prevent illicit drug trafficking that threatens the sovereignty of both countries. In answering this study, the author is a qualitative research using the theory of International Cooperation and Security Cooperation to discuss the implications of cooperation that has been carried out by the National Narcotics Board and the National Police of Timor Leste with the conclusion of Cooperation between Indonesia and Timor Leste despite the current condition of the massive drug problem, Cooperation between Indonesia and Timor Leste runs effectively with the attitude of the two countries that are cooperative and Various activities that run in accordance with the ideals of both countries.